Analisis Implementasi Kurikulum Merdeka Di Sekolah Dan Madrasah - Khoirul Muthrofin; Fathurrahman Fathurrahman (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
This article is based on the importance of implementing the Merdeka Curriculum effectively, as expected by the government to address the decline in learning due to the COVID-19 pandemic. The Merdeka Curriculum plays a crucial role in improving the quality of education in Indonesia. However, this requires readiness, planning, and effective implementation across all educational units. This study aims to analyze and describe the concept of the Merdeka Curriculum, as well as how it is implemented in schools and madrasas. The study uses a descriptive qualitative approach with a literature review research method. Data sources were obtained from various articles including books, scientific journals, legal documents, and websites. Data analysis was conducted using content analysis techniques. The research findings conclude that: first, the Merdeka Curriculum was developed by the Ministry of Education and Culture as a curriculum framework with characteristics that are more flexible, focusing on essential content, character development, and student competency. Second, the implementation of the Merdeka Curriculum in schools focuses on developing national character based on the Strengthening the Pancasila Student Profile Project (P5). Meanwhile, in madrasas, the implementation of the Merdeka Curriculum is oriented towards religious moderation based on the Strengthening the Pancasila and Rahmatan Lil Alamin Student Profile Project (P5 RA), which underpins every learning process. The Merdeka Curriculum is designed to enhance the quality of education and depicts the educational output needed to address Indonesia's educational challenges in the future.